Implikasi Hukum Praktik Perkawinan Adat Suku Baduy Dalam Perspektif Hukum Islam Dan Hukum Positif - kholis, Nurkholis (STAI Publisistik Thawalib Jakarta, 2022)
Marriage is a natural law that must occur and be carried out by every human being without exception, including for the people of the Baduy Tribe. For the Baduy tribe who adhere to customs and culture, marriage is arranged in such a way that the procedure must be in accordance with applicable customary provisions. The procedure for marriage, starting from the proposal process to fostering a household, is regulated in the binding provisions of Baduy customary institutions. The bride and groom are chosen by their parents, in practice the bride and groom will pronounce the creed, witnessed by Naib as the head. The marriages they carry out are not registered or do not have a marriage book, as is generally the case for marriages carried out by citizens in Indonesia, this is because they collide with what they believe. The implementation of the marriage contract and reception for the bride and groom was carried out at the Traditional Hall led by Pu'un to ratify the marriage. In terms of the marriage system, the Baduy people do not recognize polygamy and divorce. However, they are only allowed to remarry if one of them dies.